Play and learn: digital traditional games for vocabulary mastery in young learners - Ahmad Syawaluddin; Nur Aeni (Discover Education)
Abstract This study looks at how utilizing digital versions of classic games specifically Snakes and Ladders can help young learners learn more vocabulary in English. The study focuses on how digital versions of classic games can improve primary school students' vocabulary learning and retention. A quasi-experimental approach was used, with a control group receiving traditional vocabulary training and an experimental group acquiring vocabulary through a computerized Snakes and Ladders game. Pre- and post-tests were used to assess vocabulary retention and knowledge, and interviews were done to find out how students felt about the game-based learning approach. The experimental group's vocabulary scores significantly improved, according to the data, and the proportion of students rated as "Excellent" increased noticeably. The paired sample T-test revealed a significant statistical difference between the pre-test and post-test scores (p < 0.05), supporting the effectiveness of digital traditional games in vocabulary learning. Student feedback highlighted increased engagement, enjoyment, and motivation, although some challenges, such as the difficulty of reaching the game's goal, were noted. Suggestions for improving the game included adding more visuals, simplifying the rules, and introducing game levels for increased challenge. Overall, this study demonstrates that digital traditional games can provide an engaging and effective tool for enhancing vocabulary learning among young learners.